2020
DOI: 10.1093/tropej/fmaa072
|View full text |Cite
|
Sign up to set email alerts
|

Lipoarabinomannan Antigen Assay (TB-LAM) for Diagnosing Pulmonary Tuberculosis in Children with Severe Acute Malnutrition in Mozambique

Abstract: Background Tuberculosis (TB) and malnutrition are important causes of morbidity and mortality in children in the developing world. Aims To assess the prevalence of pulmonary TB in severely malnourished children and evaluate TB detection using the urine lipoarabinomannan antigen assay (TB-LAM). Methods A retrospective analysis was conducted in all pediatric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The study could not evaluate nutritional factors, although previous studies have indicated an association between TB and nutritional status that may affect treatment outcomes. [12,23] Future studies should look to integrate findings from the TB register and HIV database for TB/HIV co-infected patients and collect socioeconomic and nutritional status for a complete evaluation of prognostic factors.…”
Section: Researchmentioning
confidence: 99%
“…The study could not evaluate nutritional factors, although previous studies have indicated an association between TB and nutritional status that may affect treatment outcomes. [12,23] Future studies should look to integrate findings from the TB register and HIV database for TB/HIV co-infected patients and collect socioeconomic and nutritional status for a complete evaluation of prognostic factors.…”
Section: Researchmentioning
confidence: 99%
“…From included manuscripts (appendix pp 26–33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ), nasopharyngeal aspirate (ten studies 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ), oral swabs (18 studies 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ), and other (mouthwash three studies, 71 , 72 , 73 nasal swabs one study, 74 saliva four studies, 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…Existing data demonstrate that malnutrition is common among children with TB ( 6 , 7 , 9 , 21 ) and vice versa ( 22 , 23 ), with mortality tending to increase when these two diseases co-occur ( 24 ). In our survey, children in the TPA group had a higher incidence of malnutrition, reaching 69.5% (82/118).…”
Section: Discussionmentioning
confidence: 99%